Mapping of red alert assembly constituencies in Uttar Pradesh: A spatial analysis - Rohit Kumar; Arun Kumar Singh (National Geographical Journal of India, 2022)
The present study focuses on spatial patterns of Red Alert Assembly constituencies in the Uttar Pradesh Assembly elections 2012/2017. Red alert constituencies are referred to as those constituencies in which at least three contestants have mentioned heinous criminal charges against them in their election affidavit. Out of 403 Assembly constituencies in Uttar Pradesh, 121 (30.02 percent) in 2012 and 152 (37.69 percent) in 2017 were identified as red alert constituencies. These constituencies were unevenly distributed in the state. The objective of the present study is to examine the spatial pattern of red alert constituencies and voter turnout of such constituencies in the Uttar Pradesh Assembly elections of 2012/2017. The study is based on secondary data sources such as reports from the Association of Democratic Reforms (ADR) and the Election Commission of India. For the purpose of analysis, the aggregate data analysis approach has been adopted, which is one of the most rational approaches to electoral geography. The study demonstrates that contestants with criminal backgrounds were preferred by major political parties for having a high winning probability and self-bearing election expenditure. This shows the hypocritical behavior of political parties manifesting against corruption and crime and assuring good governance. The highest share of such constituencies has been recorded in Bundelkhand and the lowest in the western region. The state electoral politics is thus gradually getting affected by criminal background candidates.